Inovasi Media Pembelajaran 3 Dimensi Berbasis Teknologi pada Pembelajaran Biologi: (Technology-Based 3 Dimensional Learning Media Innovation in Biology Learning) - Najihah Fakhirah Siregar; Ghina Rohmatulloh; Riandi Riandi; Ari Widodo (BIODIK, 2022)
Covid-19 outbreak in the country has hit various public sectors which have an impact on various problems and crises. The spread of the COVID-19 pandemic has made the whole world feel difficult and forced to start learning through technology in a unique way with distance learning methods in a network or online system. One way to help the effectiveness of distance learning is to use interactive learning media. learning especially in biology lessons, including: 3D learning media, interactive videos, virtual laboratories, website-based learning media and others. Three-dimensional media is media without projections whose visual presentation is three-dimensional. This media can be tangible as real objects, both living and inanimate, and can be tangible as imitations that represent the original. However, one of the drawbacks of 3D learning media is that they cannot see a process. The research method in writing this article is by applying qualitative methods with literature studies. Based on the results of the study, it was found that 3-dimensional media integrated with process animation videos and additional features of text, audio, and website links can be an alternative interactive learning media that can clarify subject matter that is difficult to convey conventionally. It is hoped that this 3-dimensional learning media innovation can strengthen students' conceptual understanding of a material and train students' self-regulated learning. Key words: learning media, 3 dimensions, biology, technology Â  ABSTRAK Wabah Covid-19 di tanah air menerjang berbagai sektor publik yang berdampak dengan berbagai masalah dan krisis. Meluasnya pandemi wabah covid-19 membuat seluruh dunia merasa kesulitan dan terpaksa dalam memulai pembelajaran melalui teknologi dengan cara unik dengan metode pembelajaran jarak jauh dalam sistem jaringan atau daring. Salah satu cara untuk membantu efektivitas pembelajaran jarak jauh maka dibutuhkan media pembelajaran interaktif. pembelajaran khususnya dalam pelajaran biologi, diantaranya: media pembelajaran 3D, video interaktif, laboratorium virtual, media pembelajaran berbasis website dan lainnya. Media tiga dimensi merupakan media tanpa proyeksi yang penyajiannya secara visual tiga dimensi. Media ini dapat berwujud sebagai benda asli baik hidup maupun mati, dan dapat berwujud sebagai tiruan yang mewakili aslinya. Akan tetapi, salah satu kekurangan dari media pembelajaran 3D adalah belum bisa melihat suatu proses. Metode penelitian dalam penulisan artikel ini dengan menerapkan metode kualitatif dengan studi literatur. Berdasarkan hasil telaah, didapatkan bahwa media 3 dimensi yang diintegrasikan dengan video animasi proses serta tambahan fitur teks, audio, dan link website ini dapat menjadi alternatif media pembelajaran interaktif yang dapat memperjelas materi pelajaran yang sulit disampaikan secara konvesional. Harapannya inovasi media pembelajaran 3 dimensi ini dapat memperkuat pemahaman konsep siswa terhadap suatu materi serta melatih self-regulated learning siswa. Kata kunci: media pembelajaran, 3 dimensi, biologi, teknologi